FARMERS' PREFERENCES AND SATISFACTION ON RICE SEEDS (Oryza sativa) CIHERANG VARIETY IN CENLECEN VILLAGE, PAKONG DISTRICT, PAMEKASAN REGENCY - Ibrahim Malik Maulana; Sustiyana Sustiyana; Yanti Nurmalasari (Universitas Islam Madura, 2021)
This study aims to determine and analyze the preferences and satisfaction of farmers for the Ciherang variety rice seeds. The location of this research is in Cenlecen Village, Pakong District, Pamekasan Regency. The population in this study were all rice farmers in Cenlecen Village and the sample in this study amounted to 70 people using probability sampling technique. Based on the results of the study using the Customers Satisfaction Index (CSI), it shows the interest and satisfaction of farmers on the attributes of the amount of production and quality of rice, for plant attributes that are resistant to pests, production costs and easy to obtain. While the attributes of the ability to grow seeds in the field, ease of work, government services and product packaging. for attributes of plant form and are used to planting. To achieve the goal of farmer satisfaction with the attributes of rice planting using ciherang seeds, the results obtained are 63,62578, meaning that farmers are quite satisfied. The efficiency level of the attributes of farmers who use Ciherang rice seeds is on average above the efficiency line, only the attributes of the amount of production and quality of rice are expected to be below the efficiency line